2020
DOI: 10.4039/tce.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

Non-crop habitats serve as a potential source of spotted-wing drosophila (Diptera: Drosophilidae) to adjacent cultivated highbush blueberries (Ericaceae)

Abstract: Native to southeast Asia, the spotted-wing drosophila (Drosophila suzukii (Matsumura); Diptera: Drosophilidae) has become a major pest of small fruits in the Americas and Europe. Field studies were conducted over a two-year period (2015–2016) in cultivated highbush blueberry (Vaccinium corymbosum Linnaeus; Ericaceae) fields and adjacent non-crop habitats containing wild blueberries in New Jersey (United States of America). We tracked seasonal changes in D. suzukii adult abundance and fruit infestation througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In this study, we found that the abundance of SWD also depends on the time of the year. The greater abundance in forests is connected with the availability of wild fruits in forests (Kenis et al, 2016;Urbaneja-Bernat et al, 2020). This became even more obvious when checking the temporal pattern, which shows a strong increase towards the autumn months.…”
Section: Re Sultsmentioning
confidence: 89%
“…In this study, we found that the abundance of SWD also depends on the time of the year. The greater abundance in forests is connected with the availability of wild fruits in forests (Kenis et al, 2016;Urbaneja-Bernat et al, 2020). This became even more obvious when checking the temporal pattern, which shows a strong increase towards the autumn months.…”
Section: Re Sultsmentioning
confidence: 89%
“…Some non-crop hosts could even be responsible for maintaining D. suzukii populations in landscapes and therefore for the infestation of crop plants (Diepenbrock et al, 2016). There is increasing evidence that forest habitats serve as refuges, resource reservoirs and, finally, potential sources of D. suzukii to adjacent cultivated areas (Delbac et al, 2020b;Haro-Barchin et al, 2018;Poyet et al, 2014;Urbaneja-Bernat et al, 2020). Earlier infestation risks could occur in farms in high woodland landscapes (Pelton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that forest habitats serve as refuges, resource reservoirs and, finally, potential sources of D . suzukii to adjacent cultivated areas (Delbac et al, 2020b; Haro‐Barchin et al, 2018; Poyet et al, 2014; Urbaneja‐Bernat et al, 2020). Earlier infestation risks could occur in farms in high woodland landscapes (Pelton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They present the first result concerning oviposition and survival to emergence of D. suzukii in a spatial context within the canopy of a sweet cherry orchard. Urbaneja-Bernat et al (2020) studied the impact of noncrop habitat, primarily in wild lowbush blueberry, on the seasonal abundance/activity of adult D. suzukii and fruit infestation by larvae in nearby highbush blueberry ( Vaccinium corymbosum Linnaeus; Ericaceae) fields.…”
mentioning
confidence: 99%